Printed In-Ga-Zn-O drop-based thin-film transistors sintered using intensely pulsed white light - Lee, Wi Hyoung; Lee, Seong Jun; Lim, Jung Ah; Cho, Jeong Ho (ROYAL SOC CHEMISTRY, 2015)
We developed printed In-Ga-Zn-O (IGZO) thin film transistors (TFTs) by delivering droplets of a precursor solution using a picoliter fluidic dispensing system. Intensely pulsed white light (IPWL) was then used to sinter the printed deposits. From one to six drops, ring-like deposits with similar dimensions were formed; however, the morphologies and thicknesses of the deposits depended strongly on the droplet number. As the droplet number increased, the thickness of the IGZO thin film increased and the pile-up region at the periphery of the deposit gradually expanded. The electrical properties of the droplet-based IGZO TFT were strongly dependent on the droplet number and displayed the highest electron mobility and bias stability at three drops, which yielded good deposit thickness values both in the center and in the periphery regions of the ring-like deposits. These results will be useful for enhancing the electrical properties of TFTs based on printed IGZO films for use in the low-cost/flexible switching devices in display technologies.
Keywords: LOW-TEMPERATURE; HIGH-PERFORMANCE; SOL-GEL; CHANNEL THICKNESS; OXIDE; FABRICATION; STABILITY; DEVICES